ANTIBIOTIC-FREE PORK AS PERCEIVED BY CONSUMERS: THE IMPORTANCE OF QUALITY AND FOOD SAFETY - Magdalena Kozera-Kowalska; Jarosław Uglis (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2024)
The purpose of this study is to present consumers’ opinions on antibiotic-free pork, with a focus on their preferences and knowledge of the safety of such foods. The study aimed to determine to what extent the selected factors influence consumers’ purchasing decisions and their confidence in antibiotic-free meat products (having such a label at the time of purchase). Surveys were conducted on a sample of 1,177 people via the SurvGo platform. The research showed, there is no change in the frequency of pork purchases (usually several times a month), as well as the key characteristics for the buyer, i.e. taste qualities and habits and traditions. Customers consider the appearance of meat, its quality and price to be the three most important purchase criteria. However, the conducted analysis of knowledge regarding the distinction between the terms “antibiotic-free meat” and “raising without antibiotics” indicated a relatively low awareness in this regard, despite clear declarations of willingness to purchase meat with a label describing the desired parameters. This indicates the need to continuously educate consumers not only about the health benefits of pork, but also about the ways in which animals are kept to achieve high quality meat, including information about antibiotic-free farming. In addition, consumers perceive antibiotic-free pork as healthier than traditional meat, safe to eat, free of antibiotics, but also more expensive. Respondents are aware that such pork will be harder to find in stores, as there are few producers on the market offering such pork. Nevertheless, they say they are willing to pay 10%-20% more for pork labeled as antibiotic-free pork. It is noteworthy that for almost two-thirds of respondents (73.7%), the health benefits of eating such pork would be an important factor in their purchasing decisions.